From risk to resilience: index-based insurance as an adaptation strategy for water utilities - Silva, Greicelene Jesus da (2026)
Climate change has intensified the hydrological cycle, increasing exposure to extreme events such as droughts and floods that threaten water supply reliability and the financial stability of utilities. Prolonged droughts reduce revenues and affect dependent sectors, while floods damage infrastructure and interrupt services. These vulnerabilities jeopardize progress toward the Sustainable Development Goals, particularly SDG-6, concerning clean water and sanitation. Strengthening the resilience of water utilities has therefore become essential. One innovative approach is index-based insurance, which provides automatic payouts when a climatic or hydrologic indicator reaches critical thresholds. This mechanism reduces administrative costs, minimizes moral hazard, and enables rapid responses, making it particularly promising for developing countries with limited financial resources. The research proposes integrating water utilities perceptions of hydroclimatic risks, resilience, and management practices to develop realistic and applicable strategies. It analyzes Brazilian water utilities views on hydroclimatic risks, their willingness to pay index-based insurance, and the potential benefits and trade-offs of implementation through a case study in the FDB. By exploring these factors, the study seeks to enhance the adaptive capacity, testing index-based insurance as a tool for managing climate-related water challenges. Results show a predominantly reactive stance, with limited proactive measures despite widespread recognition of increasing climate risks. These findings highlight systemic vulnerabilities and underscore the urgent need for robust regulatory frameworks and long-term financial planning to strengthen adaptive capacity and resilience. Regarding the Brazilian water utilities\' perceptions towards index-based insurance schemes, the results show that Brazilian water utilities have a willingness to pay (WTP) of around 1% of their annual revenue for drought and flood schemes. The analysis of potential factors influencing WTP levels shows that the water utility\'s macro-region, water resource availability, and the respondent\'s gender affect the decision to bid on drought schemes. Similarly, for flood schemes, the availability of alternative sources, type of abstraction, the employee role, and the source types clearly influence bid levels. Even considering the reported challenges in implementing proactive measures, our survey-based analysis shows that some water utilities are interested in adopting a more forward-looking approach to financial preparednessparticularly through the proposed index-based insurance contracts. By exploring the integration of index-based insurance into water management portfolios in the FDB, the analysis demonstrates that these financial mechanisms can serve as an effective hedge against extreme drought events while potentially enhancing affordability for end-users. In a crescent global scenario of water scarcity and uncertainties concerning decision-making, this approach provides a promising pathway to balance these dual objectives. Overall, our results highlight that index-based insurance schemes have the potential to complement traditional water management strategies. Our findings also indicate that there is already a sufficient theoretical foundation for piloting drought-focused insurance schemes, which could be developed and tested in collaboration with Brazilian water utilities, the insurance sector, and regulatory agencies.